Bloom's Taxonomy Strategy For Students' Ability On Reading Discussion Text - Suhendro, Romi (Universitas Muhammadiyah Sumatera Utara, 2021)
The objective of the research was to find out the effect of using Blooms Taxonomy strategy on Students Ability to Reading Discussion Text. This research was conducted at SMA SWASTA ISLAM AZIZI MEDAN, on Jalan Kesatria, No.70, Kec. Medan Perjuangan, Kota Medan. The research conducted during the academic year 2019/2020. The population of this research took from the twelve grade students, which the total was 40 students. The sample was 40 student. This research, an experimental design would divided into two groups, the experimental and control group. The experimental group use Blooms taxonomy strategy, while The control group without use strategy. Control group over see, do not get better class control of the class experimental in give treatment. The Instrument of the research is written test. The result of this research showed that tobservedvalue was higher than ttable in which t-testt-table (9,552,021). The hypothesis was accepted. It means that there was a significant effect of using Blooms taxonomy strategy on Students Ability to Reading Discussion Text.